Prevalence and Diagnostic Strategies for Sarcopenia in Menopausal and Non-Menopausal Women: A Cross-Sectional Comparative Study - Li M; Yan X; Wu R; Liao Y; Zhang J; Ye Y; Xu C (International Journal of Women's Health, 2025)
Miaoyuan Li,1,2,* Xuewen Yan,3,* Rongshun Wu,4 Yanting Liao,5 Jing Zhang,3 Yufang Ye,3 Chenxia Xu6 1The First Clinical Medical College of Jinan University, Guangzhou, 510280, People’s Republic of China; 2Department of Urology, Zhongshan People’s Hospital, Zhongshan, 528400, People’s Republic of China; 3Women’s Health Department, Boai Hospital of Zhongshan, Zhongshan, 528400, People’s Republic of China; 4Department of Critical Care, Zhongshan People’s Hospital, Zhongshan, 528400, People’s Republic of China; 5Gynecology Department, Boai Hospital of Zhongshan, Zhongshan, 528400, People’s Republic of China; 6Prenatal Diagnosis Center, Boai Hospital of Zhongshan, Zhongshan, 528400, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chenxia Xu, Prenatal Diagnosis Center, Boai Hospital of Zhongshan, No. 6 Chenggui Road, East District, Zhongshan, Guangdong, 528400, People’s Republic of China, Email xuchenxia709@foxmail.comObjective: This study aimed to compare the prevalence of sarcopenia between postmenopausal and premenopausal women and evaluate the diagnostic performance of various screening methods combining anthropometric measurements and functional assessments.Methods: A total of 1630 women (794 postmenopausal, 836 premenopausal) were included. Data on upper arm circumference (AC), calf circumference (CC), and SARC-F questionnaire scores were collected. ROC curve analysis was performed to assess the sensitivity, specificity, and accuracy of individual and combined diagnostic models.Results: The overall prevalence of sarcopenia was 6.44%, with a higher prevalence in postmenopausal women (7.43%) than in premenopausal women (5.50%). Sarcopenic individuals had lower BMI and poorer functional performance. Among postmenopausal women, the SARC-F + CC combination demonstrated the highest diagnostic accuracy (AUC = 91.2), while in premenopausal women, the SARC-F + AC model was most effective (AUC = 85.53). The SARC-F + CC combination showed the best sensitivity (89.0%) and specificity (75.0%) across all participants.Conclusion: Sarcopenia is more prevalent in postmenopausal women, with menopause identified as a key risk factor. Combining SARC-F with calf circumference enhances diagnostic accuracy and is recommended for early screening in primary healthcare settings to facilitate timely interventions and improve patient outcomes.Keywords: sarcopenia, menopause, non-menopausal, prevalence, diagnostic methods, upper arm circumference, calf circumference, SARC-F questionnaire